Analisis Perencanaan Bendung Sei Lansat Daerah Irigasi Simandolak Kabupaten Kuantan Singingi - Farizki Afdalindra Ihsan; Siswanto Siswanto; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Weir is a building that serves to raise the water level of the river in order to pursue high specific energy needs, in addition to the wier also serves to divert the flow of a stream to a channel, in order to provide for the availability of water supply. Sei Lansat weir planned for the purpose of raw water supply to the irrigation area simandolak. Using design flood for 100 year =38.646 m3/det . Sei Lansat weir stability analysis. Stability in terms of stability against sliding, overtuning, and seepage flow. The results of analysis of stability against sliding is FK=3.668 >1.5, stability against overtuning is FK=3.399>1.5, and the value of analytics Lane is a safe WCR = 3.90 on the rocky ground being (gravel being).Keyword: Weir, Stability, Irrigation